Safety and efficacy of cold snare polypectomy for small colorectal polyps: A prospective randomized control trial and one-year follow-up study. Issue 23 (11th June 2021) - Ito, Takahiro; Takahashi, Keitaro; Tanabe, Hiroki; Sato, Keisuke; Goto, Mitsuru; Sato, Tomonobu; Tanaka, Kazuyuki; Utsumi, Tatsuya; Fujinaga, Akihiro; Kawamoto, Toru; Yanagawa, Nobuyuki; Moriichi, Kentaro; et al.
Abstract: Trial design: Elimination of small colorectal polyps with cold snare polypectomy (CSP) is reported to be as safe as hot snare polypectomy (HSP). The effectiveness of CSP has not been clearly defined, and the incidence of long-term recurrence has not been determined. We conducted a randomized control study and one-year follow-up study to assess their safety and efficacy. Methods: Patients with small colorectal polyps were randomized to receive CSP or HSP. Polypectomy was performed to determine the pathological curability, and patients completed a questionnaire about the tolerability of the procedure. Follow-up colonoscopy was performed to determine the local recurrence of adenoma. The major outcome was the non-inferiority of CSP to HSP in the rate of delayed bleeding and minor outcomes, including the incidence of immediate bleeding and perforation, procedural time, and the resection rate. Results: A total of 119 participants were recruited in this randomized study and underwent polypectomy. Among the 458 polyps, 332 eligible polyps were analyzed. The rate of adverse events was 0.6% (1/175) for CSP and 0% (0/157) for HSP, which showed the non-inferiority of CSP. While the complete resection rate of CSP was very high (100%), the R0 rate was not satisfactory (horizontal margin, 65.5%; vertical margin, 89.1%). Two local recurrences (2.5%) were observed in the follow-up of 80 adenomas treated with CSP. No recurrence was found in 79 lesions in the HSP group, which was not significant ( P = .06). Conclusions: Colorectal polyps were safely resected using CSP, similar to HSP. Most would agree to say that CSP is considered safer than HSP. The main question is then related to efficacy. Our results of the present study demonstrate that recurrence after CSP should be carefully managed for curative treatment. Abstract : Supplemental Digital Content is available in the text